Morphology and COI barcodes reveal four new species in the lycieus group of Calisto (Lepidoptera, Nymphalidae, Satyrinae) - Pérez-Asso, Antonio R.; Núñez-Aguila, Rayner; Genaro, Julio A. (Zootaxa, 2016)
The predominantly Greater Antillean endemic genus Calisto Hübner, 1823 is highly diversified on several islands being more species rich on Hispaniola. We conducted expeditions during five years in the Dominican Republic resulting in new findings related with lyceius species group. Material belonging to this group was examined following the traditional morphological characters employed in genus taxonomy, and the COI barcode sequences obtained were analyzed through different approaches: Neighbor Joining clustering, ABGD, Maximum Likelihood (ML), and Bayesian Inference (BI). Analysis yielded 12 groups representing putative species: eight corresponding to previously named ones and four new species which are described in the present work: C. mariposa sp. nov., C. azua sp. nov., C. victori sp. nov., and C. samana sp. nov. The results also confirmed a single taxonomic entity within C. pulchella Lathy and the conspecific nature of C. franciscoi Gali and C. hendersoni. A dichotomic key for identification of species within the group is also given. Both phylogenetic reconstruction methods (ML and BI) employing molecular data achieved similar results with the relationships among the majority of taxa being supported by some ecological and morphological features. The exceptions were C. zangis Fabricius, C. raburni Gali, and C. pulchella, grouped together in a weakly supported clade. These species possess a highly differentiated adult and immature morphology which indicates an earlier divergence.